2017
DOI: 10.1016/j.ridd.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Self-injury and aggression in adults with tuberous sclerosis complex: Frequency, associated person characteristics, and implications for assessment

Abstract: This paper adds specific examination of behavioural difficulties in adults with tuberous sclerosis complex who also have intellectual disability, a population at heightened risk of adverse behavioural outcomes which has received limited focussed examination to date. Findings support existing suggestions that there is relatively high risk for both self-injury and aggression, and provide novel insight into characteristics that may be associated with the presence of these behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 53 publications
1
28
0
3
Order By: Relevance
“…They also noted a higher risk for self-injury in individuals with ID, as did Wilde et al (2017), who also reported a higher risk for aggression in lower functioning individuals with TSC.…”
Section: The Intellectual Levelmentioning
confidence: 86%
See 3 more Smart Citations
“…They also noted a higher risk for self-injury in individuals with ID, as did Wilde et al (2017), who also reported a higher risk for aggression in lower functioning individuals with TSC.…”
Section: The Intellectual Levelmentioning
confidence: 86%
“…This diversity may reflect the TSC population. However, it is also known that both age and intellectual ability influence the manifestation of TAND behaviours, with more difficulties generally reported in individuals with intellectual disability (ID) and in children (de Vries, Hunt, & Bolton, 2007; Wilde et al, 2017). Given the significant proportion of unreported or missing data identified in the TOSCA study, the study authors proposed that the low reported rates identified in TOSCA suggested that, even in TOSCA participating centres, TAND manifestations were typically under-identified and under-treated (Kingswood et al, 2017).…”
Section: The Behavioural Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the same measures with an adult sample (all of whom had ID), rates of self‐injury were 31% (Wilde et al . ). Rates of aggression are reported to be higher than self‐injury, and prevalence estimates are more consistent, from 51 to 66% (Leclezio and de Vries ).…”
Section: Introductionmentioning
confidence: 97%